Analisis Minimalisasi Biaya Terapi Olanzapin Injeksi dan Kombinasi Haloperidol Dengan Diazepam Injeksi Pada Pasien Skizofrenia - Muhareni, Desweri (Jurnal Ayurveda Medistra, 2023)
The prevalence of schizophrenia has increased significantly from 2013 to 2018. In 2018, schizophrenia patients showed an increase of 7 per 1,000 population and around 84.9% received medication. Schizophrenic patients must take the medicine they need throughout their lives and have regular consultations with psychologists and psychiatrists. Expenditures on BPJS healthcare have increased significantly for inpatient and outpatient costs for schizophrenic patients. Therapy for the patient with acute phase of schizophrenia are the olanzapine injection (Zyprexa®) or a combination of haloperidol (Lodomer®) and diazepam intramuscularly injection. This study aims to investigate the average cost of the two therapy when the patients being treated in the acute room and also comparing both of them in their average costs. This prospective cohort study was conducted in the special regional hospital Duren Sawit for three months starting on June until August 2019. Retrieval of data from medical records, total direct costs while being treated in the acute room. There were 193 patients participated in this study, consisting of 102 patients in the olanzapine injection group and 91 patients in the combination injection haloperidol and diazepam injection group. The average direct cost for acute phase schizophrenia patients with olanzapin injection is Rp 2.446.644±814.719, which is higher than the cost of combination of haloperidol injection and diazepam injection by Rp 1.796.962,-± Rp 408.376. Cost minimum analysis showed therapy combination injection haloperidol and diazepam injection more cheaper than therapy olanzapin injection.